Analysis of Artistic Creation and Design Methods in Universities Based on Augmented Reality and 5G Communication Technology. (25th August 2022) - Li, Ying
Abstract : In order to enhance the research of art design in colleges and universities, based on the theory of augmented reality, 5G communication technology is used to conduct targeted analysis of art design and creation in colleges and universities. Through the research of feature parameter extraction, parameter consistency test, and optimization algorithm analysis on the relevant data of the art design in colleges and universities, the deficiencies of art design and creation in colleges and universities are pointed out, and relevant solutions are adopted. The results show that with the increase of distribution distance, the curve of the z value shows a linear change trend. The curve corresponding to a value has an obvious polynomial change rule. Through the analysis, it can be seen that the influence of two parameters on augmented reality needs to be considered comprehensively. As the number of iterative steps increases, the consistency curve of augmented reality shows an obvious linear downward trend. However, the increase of parameter m can improve the data changes of augmented reality consistency, and the research shows that parameter m can further promote the consistency changes of augmented reality. The gradual increase of index P n leads to a gradual decline in data P c, while the parameter P x has an opposite effect on data P c . Therefore, in order to obtain targeted data and results of 5G communication technology, it is necessary to comprehensively consider the influence of the two factors. Finally, the optimization model based on augmented reality and 5G communication technology is used to analyze and predict the relevant characteristic data of university art design, so as to verify the accuracy of the model. The research results can provide support for the application of augmented reality and 5G communication technology in other art fields.